STUDYING THE REALITY OF ADMINISTRATIVE PROBLEMS FOR MEMBERS OF THE ADMINISTRATIVE BODIES OF FIRST-CLASS FOOTBALL CLUBS FROM THE PLAYERS’ POINT OF VIEW - Ahmed Hashim Hammood; Mohanad Qasim assd; Khulood Jumaah Qasim; Halah Atiyah; Ahmed Amer Abdulhussein; Tamara Sabah krouk; LAYTH Farhan FARAJ; ASRAA SALAH; Alaq Hussain Munshed; Tiba Saleem AbdulMageed; Niam Riadh Hasib; Omar waleed abdulkareem; et al. (Proximus Journal Publishing, 2024)
The research aims to study the administrative problems in the sports management of the members of the administrative bodies of the first-class clubs of the province of Baghdad in football. The researchers used the descriptive approach (survey study) for its relevance to the nature of the research
Keywords: administrative problem; administrative bodies; football